The Impact of the Pandemic to Indonesian Households: Social Accounting Matrix Analysis - Gumilar, Cahya; Resosudarmo, Budy P. (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
COVID-19 is the pandemic that not only triggers a health crisis but also suppresses its economics. Due to the pandemic uncertain duration and immeasurable economic losses, this paper attempts to simulate the short run pandemic economic impact on Indonesia, particularly at the household level. This paper will employ Social Accounting Matrix (SAM) using Constrained Fixed Price Multiplier (CFPM) method to channel the pandemic impact and bring the result to the household microsimulation. Three time-based scenarios are considered, with two severity level sub scenarios for each scenario. The pandemic will be simulated entering the economy through commodity and productivity channels, and the government policies to provide the cushion to the economic will be simulated in the last two scenarios. Based on the simulations, the pandemic slams economics and reduces households’ income, especially bottom income households in urban areas. At that point, the government economic’ stimulus become a saviour by encouraging the economics.